A new fossil mordellid (Coleoptera: Tenebrionoidea: Mordellidae) from the Yixian Formation of Western Liaoning Province, China - Liu, Ming; Lu, Wenhua; Ren, Dong (Zootaxa, 2007)
A new genus and species, Mirimordella gracilicruralis gen. et sp. nov., in the subfamily Praemordellinae of Mordellidae, is described and illustrated based on a nearly complete fossil specimen. It is from the Yixian Formation of western Liaoning Province, NE China. The diagnosis of the subfamily Praemordellinae is emended based on this new species. Characters such as simple and linear maxillary palpi, simple claws, simple penultimate segments of fore and middle tarsi, small hind coxal plates, slender hind femora, only apical ridges on hind tibiae and tarsi, and no elongated last tergum suggest that Praemordellinae might be the precursor of modern mordellids. The resemblance between the new species and the Late Jurassic Praemordella martynovi indicates close relationships between them and with the tribe Stenaliini in the subfamily Mordellinae. The position of epicoxa and slender hind femur suggest that the new species may be more primitive than Praemordella martynovi and may indicate the age of the Yixian Formation no later than Late Jurassic.